Science Fun Learning for the Students Affected of Natural Disasters - Kismiati, Dyah Aniza (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Fun learning will attract students to classroom learning activities learning, especially for victims of natural disasters. Students who experience natural disasters fear doing various things at home and outside the home (school). This study aims to find out whether fun science learning carried out by planting plants can improve students' understanding of learning science. This quantitative descriptive research uses test instruments to measure students' knowledge of family medicinal plant material. The population in this study was elementary school students who were victims of the earthquake natural disaster earthquake in 2022, while the research sample was 15 elementary school students. This sampling is done randomly. The data obtained were analyzed descriptively to determine improved student understanding of learning science. The results of data analysis showed that science fun learning applied through outdoor learning activities by planting family medicinal plants can increase students' understanding related to science material. However, the improvement is categorized as low based on the N-gain score 0.2. The recommendation of this study is to improve student understanding of when fun science learning should be supplemented with other methods by referring to the local wisdom of participants. Thus, the feeling of trauma that saddens the survivors will be slightly forgotten with fun activities and education.